Matriz do fluxo de comércio interestadual do Estado do Ceará: uma análise do período de 2011 a 2014 - Moura, Denise de Andrade (2015)
This study aims to examine the relations of interstate commerce between the State of Ceará and the others states in Brazil, between 2011 and 2014. In order to add new information to the research in the area, was used in this work as the primary data source the Electronic Invoice, mandatory use in interstate operations from December 1, 2010. The interstate trade operations were grouped according to the Economic Activities National Classification - CNAE of the participants, as well as the products marketed were related according to the degree of technological intensity based on the OECD classification. From this perspective, it identified the nature of economic activities of importers and exporters of the state, as well as the degree of economic interdependence between Ceara and other states. It was found that the Ceará presents economic dependence on trade with the Southeast, specifically with the State São Paulo, the main supplier, even geographically distant, products with technological medium-high intensity. On the other hand, Ceará has preponderance on exports to the neighboring states of low technology products. Finally, the state records a surplus relationship mainly to Maranhao, Rio Grande do Norte, Piauí and Sergipe in the Northeast region and a deficit with South and Southeast.